THE PROPERTIES OF RECYCLED RUBBER FROM WASTE TIRES IN THE PRODUCTION OF CEMENT COMPOSITES - SVOBODA, Jakub; VÁCLAVÍK, Vojtěch; DVORSKÝ, Tomáš; MÁČALOVÁ, Kateřina; CHARVÁT, Jakub; GOLA, Lukáš (GeoScience Engineering, 2020)
This article presents the results of a study dealing with the use of a combination of recycled rubber from waste tires as a 100% substitute in the production of cement composites. Aggregate was replaced with recycled rubber in two ratios, namely the ratio of 50/50 and the ratio of 40/60 of the share of fraction 0/1 mm and fraction 1/3 mm. The designed formulas of cement composites were subjected to the tests of their physical and mechanical properties in order to determine the properties of the used recycled rubber combination. The tests included the consistency of the grain curve, mixing water properties, consistency of cement mortar, and strength characteristics (tensile flexural strength and compressive strength). The study presents results that are fundamentally different from the comparative samples and their use in the building industry; however, at the same time, they open up new possibilities of their utilization as a building material. Keywords: Composite; Concrete; Mixing water; Recycled rubber granulate; Waste tire DOI 10.35180/gse-2020-0028